The Application of Admit and Exit Slips Teaching Technique in Improving the Students’ Writing Skill at STKIP YPUP - Sulfaedah Lestari; Abidin; Nasmilah (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
The research aims at investigating whether the application of the Admit and Exit Slips teaching technique can improve the writing skill of the students of class BI 4.2 STKIP YPUP Makassar. The research used the pre-experimental method by performing a pre-test and post-test. The populations were the students of class BI 4.2 STKIP YPUP Makassar. The samples were as many as 20 students. The independent samples t-test indicates a significant improvement group after the treatment (the t-observed value and the sig.tailed are lower than 0.05 in the significance level of 2.093<12.22). this shows that the mean score of the post-test is greater than the pre-test (77.7>68.4). The improvement can also be seen in the five components in writing namely: the content, vocabulary, language use, organization, and mechanics. In which result of the post-test is greater than the pre-test. This implies that the students’ writing skill gets better. It can be concluded that the Admit and Exit Slips teaching technique can improve the students’ writing skill and this offers a significant pedagogical implication that needs to be empowered by Indonesian EFL teachers.